Early Health Economic Evaluation of Medical Devices - Khoudigian-Sinani, Shoghag (My University, 2018)
ABSTRACT Background and objectives To avoid unsuccessful implementation of new health technologies in clinical practice, it is important to investigate their potential cost-effectiveness before adoption, using the health technology assessment (HTA) process. Cost-effectiveness analysis (CEA) techniques tailored for the early stages of a health technology when there is limited evidence available, may guide more efficient resource investment in the development process, such as conducting additional studies that would inform key parameters to strengthen the economic model. However, knowledge and application of early CEA has been limited. A key challenge is trying to conceptualize an economic model with limited information regarding a product’s exact use in clinical practice, and how to use the existing limited data as input parameters for the model. In this thesis, early CEA refers to the premarket stage of a product’s lifecycle. The objective of this thesis was to develop a guiding framework for conducting early-CEA for medical devices with limited evidence, by contextualizing all of the available methods in the literature, in order to help support conducting early-CEA and to increase its usefulness. Methods Project 1: A systematic review was conducted with the purpose of identifying and critically appraising all of the available methods for conducting early-CEA for medical devices with limited evidence, and to propose a conceptual guiding framework to conduct robust early-CEA. Project 2: Appropriate methods identified in the systematic literature review from project 1 were applied to conduct an early-CEA of StraticyteTM, a novel prognostic tool, when used in combination with the current standard of care (SOC), histopathology, for diagnosing oral potential malignant or pre-malignant lesions (OPLs) in adults aged 35 years or older from a private and patients’ perspective. Project 3: The lifetime costs, patients’ outcomes, and cost effectiveness of StraticyteTM in combination of histopathology compared to histopathology alone among oral cancer patients were assessed in an economic evaluation from the public payer perspective, by using the output from project 2 as a starting point. Results Project 1: Thirteen methods from 26 studies were identified and grouped based on their purpose in conducting CEAs with limited evidence. Based on these methods, a step-wise conceptual guiding framework of how to conduct CEA for medical devices with limited evidence was created, where the methods were introduced at each step based on their general aim for conducting CEA. Project 2: The early-CEA demonstrated a high probability that StraticyteTM and histopathology will be cost-effective for the detection of OPLs, which in turn encourages continued investment by manufacturers into the product, and suggests that future investment by the healthcare system and individual patients may be worthwhile. Project 3: The long-term economic evaluation demonstrated potential beneficial downstream effects to the healthcare system from introducing StraticyteTM to current clinical practice; due to fewer cancer cases requiring treatment over the long-term. This highlighted the considerable cost savings to the public healthcare system, if payers invest in a preventative technology in dentistry that could have downstream effects on publically funded cancer care. Conclusions The conceptual guiding framework of early-CEA of medical devices with limited evidence that was developed in this thesis classified and harmonized the available methods to support the utilization of early-CEA for key stakeholders in medical device development, and implementation. The premarket assessment of StraticyteTM demonstrated the high probability of it being cost-effective, which may encourage investment for manufacturers, and for public payers, in this health technology. The long-term CEA demonstrated the potential positive downstream impact of StraticyteTM on the healthcare system as a result of its adoption in the market. Further, given that StraticyteTM is developed for use in dentistry, a privately funded healthcare service, this thesis highlights the advantage of public payers’ investment in preventive health technologies in dentistry that have downstream effects in the publically funded medical healthcare system.
Early Health Economic Evaluation of a Novel Medical Device and the Development of a Conceptual Guiding Framework